Pengaruh Praktik Kerja Lapangan dan Perencanaan Karir terhadap Kesiapan Kerja Peserta Didik Kelas XII di SMKN 31 Jakarta - Ayu Wulandari; Puji Wahono; Muhammad Ikhwan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2026)
This study aims to determine the effect of Field Work Practice (PKL) and Career Planning on the Job Readiness of grade XII students at SMKN 31 Jakarta. The research employed a quantitative method with a survey approach. The population consisted of all grade XII students of SMKN 31 Jakarta, and a saturated sampling technique was applied so that the entire population became the research sample. Data were collected through questionnaires using a Likert scale and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination with the assistance of IBM SPSS. The results indicate that Field Work Practice has a positive and significant effect on Job Readiness, with a t-value of 9.967 and a significance value of 0.000 (<0.05). Career Planning also has a positive and significant effect on Job Readiness, with a t-value of 8.318 and a significance value of 0.000 (<0.05). Simultaneously, Field Work Practice and Career Planning significantly influence Job Readiness, as indicated by an F-value of 88.543 and a significance value of 0.000 (<0.05). The regression equation obtained was Y = -1.782 + 0.638X₁ + 0.450X₂. The coefficient of determination (R²) of 0.571 shows that both variables contribute 57.1% to Job Readiness, while 42.9% is influenced by other factors. The findings suggest that better implementation of PKL and more mature Career Planning are associated with higher levels of student Job Readiness.